Two rapid appraisals of FAO-56 crop coefficients for semiarid natural vegetation of the northern Ethiopian highlands - Descheemaeker, Katrien K.; Raes, Dirk; Allen, R.; Nyssen, Jan; Poesen, J.; Muys, B.; Haile, M.; Deckers, J. (Elsevier, 2011)
In the highlands of northern Ethiopia, degraded hillslopes are closed for grazing and agriculture for environmental rehabilitation. In order to assess the effect of these exclosures on water balances, a correct assessment of evapotranspiration is needed. A common method for calculating evapotranspiration employs the reference evapotranspiration in combination with a crop coefficient. However, for natural vegetation, these crop coefficients are not readily available. Therefore, the objective of this study was to derive crop coefficients for semiarid natural vegetation using two different approaches. The crop coefficients were assessed with the dual crop coefficient approach as outlined in the FAO Irrigation and Drainage Paper n°56 and compared with crop coefficients derived from a simple soil water balance. A good agreement between both methods was found. The mid-season crop coefficients ranged from 0.50 to 0.85 for open vegetation with small shrubs and from 0.85 to 0.95 for well developed shrubland. Vegetation with a closed tree canopy was characterized by a mid-season crop coefficient between 0.95 and 1.1. Additionally, a significant logarithmic relation between vegetative soil cover and crop coefficient was found. Using this relation, crop coefficients can be easily derived for semiarid shrub savannahs in similar environments and used for the calculation of evapotranspiration.